THEORETICAL PRINCIPLES OF LAND REFORM IN UKRAINE FROM THE STANDPOINT OF SOCIAL REPRODUCTION AND RUSSIAN MILITARY AGGRESSION - Zakharchenko, V.I. (The actual problems of regional economy development, 2023)
The article is devoted to substantiation and revision of theoretical principles of land reform in Ukraine. The need for this arose due to the fact that the Ukrainian model of the land market and certain land reform measures "conflict" with the fundamental theoretical provisions in the field of land relations as an important component of public relations. This conflict was further aggravated against the backdrop of unprecedented violation of the processes of public reproduction due to the full-scale invasion of Russia in Ukraine. The purpose of the study is to systematize and deepen the theoretical foundations of land reform in Ukraine from the standpoint of social reproduction and Russian military aggression. The study mainly uses general scientific methods: abstraction, analysis and synthesis, logical generalization and comparison. To represent the processes of reforming land relations from the standpoint of social reproduction, the method of functional analysis is used. In the article, the theory of reforming land relations is presented in the historical aspect and in the context of stages of social reproduction (production, distribution, exchange and consumption). Land ownership relationships are considered within theories of land rent, property rights, and constitutional economics. The priority of national ownership of land is emphasized. The relations of land turnover are presented with an emphasis on the theories of free market, transaction costs and economic benefits. This made it possible to state that the Ukrainian model of the land market should be based on the national form of land ownership. Land use relationships are analyzed based on economic risk theories, real estate cycles, and an optimal contract. It is concluded that the optimal can be not only transactions on the purchase and sale of land, but also the transfer of rights to use it. Production land relations are considered in terms of theories of factors of production, labor value (including on the basis of the school of physical economy), etc. It is emphasized that land is a natural asset that has the properties of functional capital. The scientific novelty of the study is that it presents the theoretical foundations of land reform in Ukraine in a functional aspect - in terms of stages of social reproduction - taking into account the influence of Russian military aggression on it. The presented theoretical concept of land reform in Ukraine can help solve most of its acute problems, in particular, the sale of land to legal entities with foreign capital.